Development and Feasibility Testing of Virtual Reality Based Learning Media for Practicum in LAN and Fiber Optic Network Cabling Using the 4D Model - Setiawan, Arif; Ulinnuha, Muhammad (Universitas Muhammadiyah Surakarta, 2026)
This study aims to develop and evaluate the feasibility of Virtual Reality (VR)–based learning media for practicum activities in Local Area Network (LAN) and Fiber Optic (FO) cabling. The method employed was Research and Development (R&D) using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. Three-dimensional assets were developed using Blender and integrated into Unity 3D with the C# programming language, then implemented on Oculus devices to produce an interactive and immersive virtual laboratory simulation. The feasibility testing was conducted through validation by media experts and subject-matter experts, as well as user trials employing the System Usability Scale (SUS). The results of expert validation showed a percentage of 88% from media experts and 92% from subject-matter experts, both categorized as highly feasible. User testing involving 20 students yielded an average SUS score of 70 (grade C/OK), indicating that the application is acceptable and suitable for use. The findings demonstrate that the VR media is capable of realistically visualizing the procedures of LAN cable crimping and fiber optic slicing, thereby supporting students’ conceptual understanding and practical skills. Therefore, this VR-based learning media is feasible to be utilized as an innovative alternative in computer network practicum learnin.